Graphene‐Enabled Electrophoretic Ion Pump Delivery Devices. Issue 12 (26th February 2022) - Seitanidou, Maria; Sygletou, Maria; Savva, Kyriaki; Berggren, Magnus; Stratakis, Emmanuel; Simon, Daniel T.
Abstract: Organic electronic ion pumps (OEIPs) have been investigated as a promising solution for precise local delivery of biological signaling compounds. OEIP miniaturization provides several advantages, ranging from better spatiotemporal control of delivery to reduced invasiveness for implanted devices. One miniaturization route is to develop OEIPs based on polyelectrolyte‐filled capillary fibers. These devices can be easily brought into proximity of targeted cells and tissues and could be considered as a starting point for other "iontronic" implants. To date, OEIPs and other such iontronics exhibit a limited electrode capacity as they generally rely on poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) electrodes. While this material is well studied and viable in mixed ion‐electron systems, its bulk capacitance is limited by eventual redox reactions. Graphene is an excellent alternative for high‐performance electrodes and low‐cost solution‐processed graphene derivatives are particularly promising, exhibiting high charge mobility and ideal structural properties (lightness, flexibility). Here, the application of solution‐processed reduced graphene oxide (RGO) as high‐performance driving electrodes for OEIPS is presented. RGO electrodes are characterized and compared with standard PEDOT:PSS (and Ag/AgCl) electrodes. The RGO exhibits greater charge storage capacity and thus increased operational lifetime. The graphene‐enabled OEIPs exhibit improved neurotransmitter transport, without imposing limitations to the applied current level. Abstract : The first successful marriage of the well‐developed iontronics toolkit with the equally promising and developing world of graphene‐based electronics is reported. Graphene electrodes can provide multiple advantages (longevity, electrode capacity, processability) over previous electrode materials used in iontronics. Devices are demonstrated capable of reliable transport of the neurotransmitter GABA, one of the most challenging substances is delivered using iontronics.